The correlation of brainwaves of Taekwondo athletes with training vis-à-vis competition performance – an explorative study. (2nd January 2018) - Chu, Dachen; Chen, Li-Jung; Lee, Ya-Ling; Hung, Bao-Lien; Chou, Kuei-Ming; Sun, Ai-Chi; Fang, Shih-Hua
Abstract: Various studies have reported the correlation between brainwaves electroencephalogram (EEG) and various sports. However, until now, the correlation between EEG signals and the Taekwondo (TKD) have not been reported. The aim of this study is to investigate the correlation of brainwaves of TKD athletes in training experiences and competition performance. The EEG signals were collected from 12 elite male TKD athletes. The β -wave was significantly increased when the heart rate of participant was >120 min −1 compared to the resting state. The γ -wave was significantly decreased during foot kicking modalities. In addition, the γ -wave was significantly increased while watching competition films when compared to that in resting state. In the simulation game, before the first and second round, the δ -wave of the winner group was significantly higher, whereas the α -and γ -waves were significantly lower than those of the loser group. While before the third round, the θ -wave of the winner group was significantly lower. This study showed that EEG signals were significantly different during the training experiences versus the simulated game of TKD. The results of this study also sheds light on training methods for improving sport performance in future programmes.